Geometrical effect on the behavior of circular and elliptic tubes under dynamic axial loading - Fauziah, Mat; Rakhmad Arief, Siregar, Dr.; Khairul Azwan, Ismail, Dr.; Sazali, Yaacob, Prof. Dr.; Othman, Inayatullah, Capt (Rtd) Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.